2009
DOI: 10.1371/journal.pone.0005388
|View full text |Cite
|
Sign up to set email alerts
|

Non-Canonical Wnt Signaling and N-Cadherin Related β-Catenin Signaling Play a Role in Mechanically Induced Osteogenic Cell Fate

Abstract: BackgroundUnderstanding how the mechanical microenvironment influences cell fate, and more importantly, by what molecular mechanisms, will enhance not only the knowledge of mesenchymal stem cell biology but also the field of regenerative medicine. Mechanical stimuli, specifically loading induced oscillatory fluid flow, plays a vital role in promoting healthy bone development, homeostasis and morphology. Recent studies suggest that such loading induced fluid flow has the potential to regulate osteogenic differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
134
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(142 citation statements)
references
References 78 publications
6
134
0
2
Order By: Relevance
“…Interestingly, at the same time, C/EBP-a and PPAR-g expression was reduced in these cells, indicating that WNT3A is an important regulator in the determination of stem cells into myocytes versus adipocytes (Shang et al 2007a,b). In terms of osteogenesis, our own experiments as well as the studies performed by independent groups showed that non-canonical WNT5A signalling induces multipotent mesenchymal stem cells to undergo osteogenesis, while simultaneously adipogenesis is inhibited (Arnsdorf et al 2009, Bilkovski et al 2010, Santos et al 2010. Furthermore, the osteopontin promoter was found to be up-regulated by WNT5A, suggesting a molecular mechanism by which this WNT family member exerts pro-osteogenic effects (Bilkovski et al 2010).…”
Section: Wnt Molecules In the Determination Of Preadipocytesmentioning
confidence: 65%
“…Interestingly, at the same time, C/EBP-a and PPAR-g expression was reduced in these cells, indicating that WNT3A is an important regulator in the determination of stem cells into myocytes versus adipocytes (Shang et al 2007a,b). In terms of osteogenesis, our own experiments as well as the studies performed by independent groups showed that non-canonical WNT5A signalling induces multipotent mesenchymal stem cells to undergo osteogenesis, while simultaneously adipogenesis is inhibited (Arnsdorf et al 2009, Bilkovski et al 2010, Santos et al 2010. Furthermore, the osteopontin promoter was found to be up-regulated by WNT5A, suggesting a molecular mechanism by which this WNT family member exerts pro-osteogenic effects (Bilkovski et al 2010).…”
Section: Wnt Molecules In the Determination Of Preadipocytesmentioning
confidence: 65%
“…Activation of these pathways plays an essential role in MSC fate determination between adipogenic, chondrogenic, and osteogenic lineage pathways and in activating the osteogenic genes necessary for bone lineage differentiation, such as Runx2. (47,48) A recent paper by Arnsdorf et al (64) also demonstrated that noncanonical Wnt signaling, particularly with respect to Wnt5a, Ror2, and RhoA, plays an important role in fluid flow-induced osteogenesis. Therefore, activation of noncanonical Wnt by mechanical loading may have the clinical benefit of preserving bone mass with synergistic and collective functions, including an enhancement of Runx2 expression leading to osteogenesis, a reduction in PPARg activity leading to the inhibition of adipogenesis, (58) and an increase in OPG expression leading to the prevention of potential osteolysis.…”
Section: Discussionmentioning
confidence: 98%
“…GDF5 and GDF8 are involved in chondrogenesis and callus formation. Additionally, GDF8, a negative regulator of skeletal muscle growth, stimulates the adipogenic differentiation in MSCs, whereas its absence increases osteogenic differentiation (Artaza et al, 2005;Hamrick et al, 2007). Interestingly, a positive correlation of GDF8 deficiency and fracture callus size in a mouse in vivo model was reported (Kellum et al, 2009).…”
Section: A B Em Czekanska Et Almentioning
confidence: 99%
“…Wnt4 gene expression was detectable in control samples and in treated cells from 2 donors (5 and 8); whereas Wnt5a, 7b and β-catenin were expressed in stimulated and unstimulated cells. Both Wnt3a and Wnt4, together with β-catenin, are involved in the canonical Wnt pathway stimulating the expression of alkaline phosphatase (ALP), osteocalcin (OC), BMP2 and Runx2 (Kim et al, 2013), and inhibiting the non-canonical Wnt pathway (Boland et al, 2004). Importantly, the effect of canonical Wnt signalling on osteogenesis is highly dependent on the stage of target cells (Ling et al, 2009).…”
Section: A B Em Czekanska Et Almentioning
confidence: 99%